The Poetics of Time and Memory in Shoyim Butayev’s Novels “Qo‘Rg‘Onlangan Oy” and “Shox” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes the artistic interpretation of time and memory in Shoyim Butayev’s novels “Qo‘rg‘onlangan oy” and “Shox.” The study aims to reveal the function of memory as the main mechanism organizing the plot, the fragmented structure of artistic time, and the relationship between individual and collective memory. As a result of the analysis, it is substantiated that time in these novels is represented not as a chronological sequence, but as a psychological and philosophical category.